DETERMINATION OF WORK PRODUCTIVITY AND SERVICE QUALITY: EDUCATION LEVEL AND COMPETENCE ANALYSIS LITERATURE REVIEW - Mirawati, Mirawati; Hapzi Ali (Dinasti International Journal of Digital Business Management, 2022)
Previous research or relevant research is very important in a research or scientific article. Previous research or relevant research serves to strengthen the theory and phenomena of the relationship or influence between variables. This article reviews the Determination of Work Productivity and Service Quality: Analysis of Education Level and Competence, A Study of Human Resource Management Literature. The purpose of writing this article is to build a hypothesis of the influence between variables to be used in further research. The results of this library research are that: 1) Education level has an effect on Work Productivity; 2) Competence affects Work Productivity; 3) Education level has an effect on Service Quality; 4) Competence affects Service Quality; and 5) Work Productivity has an effect on Service Quality.